Alveolar osteotomy associated with resorbable non‐ceramic hydroxylapatite or intra‐oral autogenous bone for height augmentation in posterior mandibular sites: a split‐mouth prospective study. Issue 9 (13th July 2012) - Kawakami, Paulo Y.; Dottore, Alexandre M.; Bechara, Karen; Feres, Magda; Shibli, Jamil A.
Abstract Background The presence of the inferior alveolar nerve within the body of the mandible could jeopardize the placement of dental implants. Previous studies have shown that the interpositional osteotomy for posterior mandible ridge augmentation could be a predictable procedure. Nevertheless, there are few prospective, controlled, and randomized studies that evaluated this technique using different bone graft materials. Purpose This prospective, controlled split‐mouth study evaluated, using tomographic and Resonance Frequency Analyses (RFA), implants placed in the augmented mandibular area. Material and methods Alveolar augmentation osteotomies were performed bilaterally in 12 partially edentulous mandibular patients in a split‐mouth design. The alveolar segmental osteotomies were assigned in two groups: test group, interpositional non‐ceramic hydroxylapatite bone graft, and control group, interpositional intra‐oral autogenous bone graft. After 6 months healing, implants were placed. The tomographic measurements of bone gain were recorded at baseline and 6 months after surgery, when the implants were placed. At 12 months after osteotomy, RFA were performed for each implant. Results The mean of bone gain 6.5 ± 2.4 mm and 7.0 ± 1.76 mm to control and test group, respectively (P > 0.05). RFA values between groups were similar at baseline and 12 months follow‐up (P > 0.05). Conclusion Alveolar osteotomies associated with sandwich interpositional bone graft, independently of bone graft, resulted in bone formation over a period of 12 months.